A polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material
By copolymerizing on nanocellulose, quaternary ammonium functionalized nanocellulose materials are prepared and combined with polyvinyl alcohol and iron tannin to form a high-strength, antibacterial food packaging material, solving the problem of insufficient barrier properties and antibacterial properties of existing materials and achieving efficient food packaging performance.
Patent Information
- Application Number
- CN202211704831.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-12-29
Smart Images

Figure CN116218110B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation and development of food packaging materials, and mainly to a preparation method and application of a polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material. Background Art
[0002] Natural polyvinyl alcohol materials have the advantages of being biodegradable and non-toxic when used in food packaging, but their poor barrier and antibacterial properties have hindered their development. Therefore, it is very important to develop sustainable and high-performance polyvinyl alcohol-based food packaging materials. Cellulose is the most abundant biopolymer resource in the world and has unique intrinsic properties, such as biodegradability and environmental friendliness. In addition, nanocellulose has advantages such as a high aspect ratio, which can give the material better mechanical strength. However, as packaging materials, polyvinyl alcohol and nanocellulose both have the disadvantages of being highly hydrophilic and having poor antibacterial properties, and cannot be directly used in food packaging. At the same time, the materials commonly used for functional modification of polyvinyl alcohol and cellulose are mostly organic materials with certain toxicity. Using them to prepare food packaging materials is not conducive to food safety.
[0003] The mechanism of action of quaternary ammonium salt fungicides is mainly that cations adsorb negatively charged bacteria through electrostatic forces, hydrogen bonds, and hydrophobic binding between surfactant molecules and protein molecules, and aggregate on the cell wall, producing a chamber barrier effect, which inhibits bacterial growth and causes death; at the same time, its hydrophobic alkyl group can also interact with the hydrophilic group of bacteria, change the permeability of the membrane, and then cause lysis, destroy the cell structure, and cause cell dissolution and death. The use of hydrophobic quaternary ammonium salt compounds to functionalize and modify nanocellulose can enhance the hydrophobicity, mechanical strength and antibacterial properties of the material to a certain extent.
[0004] However, nanocellulose is currently modified by a single quaternary ammonium salt, and the antibacterial effect is still difficult to meet the actual use requirements of food packaging. The photothermal antibacterial strategy triggered by near-infrared (NIR) laser has high precision and broad-spectrum antibacterial activity, which can be used to synergistically enhance the antibacterial properties of traditional materials. The coordination complex tannic acid iron is prepared by simply mixing tannic acid solution and FeCl3·6H2O solution, and added to the material, which can effectively achieve antibacterial and antimicrobial inhibition under NIR laser irradiation. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a preparation method and application of a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material, which can effectively solve the problems of poor barrier and antibacterial properties of polyvinyl alcohol and nanocellulose, as well as the problem that the antibacterial properties of the single quaternary ammonium salt modified in the existing enhancement technology still do not meet the use requirements, and the high biological toxicity.
[0006] The present invention is achieved through the following technical solutions:
[0007] Technical solution 1. The present invention relates to a polyvinyl alcohol / nanocellulose / tannic acid iron based high-strength food packaging material, characterized in that: the material mainly comprises polyvinyl alcohol (PVA), hydrophobic quaternary ammonium salt functionalized nanocellulose (CNF-QAS) and tannic acid iron (TA-Fe): CNF-QAS accounts for 1% to 7% by mass, and TA-Fe accounts for 0.4% to 1% by mass (both calculated based on the mass of PVA).
[0008] Technical Solution 2. The food packaging material according to Technical Solution 1 is characterized in that: in the food packaging material, PVA and CNF-QAS fibers are entangled with each other to form a three-dimensional structure, and the bonding is enhanced through multiple effects such as static electricity and hydrogen bonds, giving the material higher mechanical properties and barrier properties; at the same time, through the synergistic effect of quaternary ammonium salts and ferric tannate, the material can effectively achieve antibacterial and antimicrobial properties under near-infrared laser irradiation.
[0009] Technical Solution 3. The CNF-QAS according to Technical Solutions 1 and 2 is characterized in that: the structural formula is as follows, wherein n=1~25, m=20~200.
[0010]
[0011] Technical Solution 4. A polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material according to Technical Solution 1, wherein the preparation method comprises the following steps:
[0012] Step 1, N, N-dimethyloctylamine and methanol are mixed and stirred at -20°C to dissolve; 4-vinylbenzyl chloride is slowly added, the temperature is raised to 30°C, and the reaction is carried out for 24 hours. After the solvent is removed by rotary evaporation, it is vacuum dried to obtain QAS.
[0013] Preferably, the mass ratio of N,N-dimethyloctylamine to methanol is 1:(12-18);
[0014] Preferably, the mass ratio of N,N-dimethyloctylamine to 4-vinylbenzyl chloride is (3-5):1.
[0015] Step 2, CNF is placed in a DMSO solution containing N, N'-carbonyldiimidazole, and the reaction is performed at 40°C in a light-shielded state for 24 hours, and bis(carboxymethyl) trithiocarbonate is added as a chain transfer agent and the reaction is continued at 40°C in a light-shielded state for 48 hours. Then, the obtained intermediate product is mixed with QAS and 10 mg of azobisisobutyronitrile and dissolved in DMSO, and the reaction is performed at 60°C for 18 hours, and the CNF-QAS is obtained by washing and drying.
[0016] Preferably, the concentration of the DMSO solution containing N,N'-carbonyldiimidazole is 0.2 to 0.5 mol / L;
[0017] Preferably, the mass ratio of CNF to bis(carboxymethyl)trithiocarbonate is 1:(1-2);
[0018] Preferably, the mass ratio of the intermediate product to QAS is 1:(1-1.5).
[0019] Step 3, adding PVA to the CNF-QAS solution, heating and stirring at 85-110° C. for 1-8 hours to obtain a PVA / CNF-QAS solution. Preferably, the mass ratio of CNF-QAS to PVA is (1%-7%):1.
[0020] Step 4, after the PVA / CNF-QAS solution is cooled, TA-Fe is added, and magnetic stirring is performed to obtain a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material after drying.
[0021] Preferably, the mass ratio of TA-Fe to PVA is (0.4% to 1%):1.
[0022] Technical Solution 5. A polyvinyl alcohol / nanocellulose / iron tannate-based high-strength food packaging material according to Technical Solution 1, characterized in that the macroscopic form can be a film, electrospun fiber, aerogel, paper and cardboard, or used as a powder additive in pulp molding materials.
[0023] Technical Solution 6. A polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material according to Technical Solution 1, characterized in that it can be widely used in non-directly ingested foods such as fruits and vegetables.
[0024] Compared with the prior art, the present invention has the following beneficial technical effects:
[0025] The present invention prepares QAS by copolymerization on CNF to obtain a quaternary ammonium salt functionalized nanocellulose material, which can provide certain hydrophobicity, mechanical strength and antibacterial properties for subsequent food packaging materials. Compared with the modification of a single amino functional group monomer, the use of QAS for the modification of CNF increases the number of amino functional groups, which can improve the disadvantage of weak antibacterial effect of a single grafted modified material, and will greatly improve the antibacterial ability of CNF. At the same time, the hydroxyl groups on the surface of nanocellulose and the hydroxyl groups on the surface of PVA are mutually exclusive. By means of the positively charged amino functional groups of QAS, the binding force between CNF and PVA can be further enhanced through electrostatic action, and the mechanical strength of subsequent food packaging materials can be improved through multiple forces such as van der Waals force, electrostatic action, hydrogen bonding, etc., which can effectively solve the problems of single action and poor mechanical strength in the materials prepared by existing modification technology. In addition, the introduction of QAS into the material can improve the hydrophobicity of the PVA / CNF composite material, and effectively achieve the barrier property and water resistance of the material. The coordination complex tannic acid iron was prepared by simply mixing tannic acid solution and FeCl3·6H2O solution and added to the material, which can synergistically enhance the antibacterial properties of traditional materials. Under the triggering of near-infrared laser, the material has high-precision and broad-spectrum antibacterial activity, which can effectively achieve antibacterial and antimicrobial inhibition.
[0026] At the same time, the preparation method of the present invention is simple, the reaction conditions are mild, the reactants are less toxic, and the reaction process is relatively safe. The process is both economical and simple, and can be widely used in food packaging; the prepared material has good degradability and biocompatibility, which is beneficial to the sustainable development of the environment; and the source of the reaction raw materials is wide, which is beneficial to the promotion and application of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The basic structure diagram and synthesis method of the material are shown as an abstract figure; Figure 2 It is the result of biocompatibility test; Figure 3 It is the test results of mechanical properties and barrier properties; Figure 4 It is the result of antibacterial experiment; Figure 5 It is the result of food preservation experiment. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0029] The invention discloses a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material, which is characterized in that the material mainly comprises polyvinyl alcohol (PVA), hydrophobic quaternary ammonium salt functionalized nanocellulose (CNF-QAS) and tannic acid iron (TA-Fe): the mass proportion of CNF-QAS is 1% to 7%, and the mass proportion of TA-Fe is 0.4% to 1% (both calculated based on the mass of PVA).
[0030] The present invention also discloses the structure and mechanism of the food packaging material, namely, PVA and CNF-QAS fibers are entangled with each other to form a three-dimensional structure, and the bonding is enhanced through multiple effects such as static electricity and hydrogen bonds, giving the material higher mechanical properties and barrier properties; at the same time, through the synergistic effect of quaternary ammonium salt and ferric tannate, the material can effectively achieve antibacterial and antimicrobial properties under near-infrared laser irradiation.
[0031] The present invention also discloses the CNF-QAS structural formula, as shown below, wherein n=1-25, m=20-200.
[0032]
[0033] The present invention also discloses a method for preparing the polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material, comprising the following steps:
[0034] S1, N, N-dimethyloctylamine and methanol were mixed and dissolved by stirring at -20°C; 4-vinylbenzyl chloride was slowly added, the temperature was raised to 30°C, and the reaction was carried out for 24 hours. After the solvent was removed by rotary evaporation, it was dried in vacuum to obtain QAS.
[0035] S2, CNF is placed in a DMSO solution containing N, N'-carbonyldiimidazole, and the reaction is performed at 40°C in a light-shielded state for 24 hours, and bis(carboxymethyl) trithiocarbonate is added as a chain transfer agent and the reaction is continued at 40°C in a light-shielded state for 48 hours. Then, the obtained intermediate product is mixed with QAS and 10 mg of azobisisobutyronitrile and dissolved in DMSO, and the reaction is performed at 60°C for 18 hours, and the CNF-QAS is obtained by washing and drying.
[0036] S3, adding PVA to the CNF-QAS solution, heating and stirring at 85-110° C. for 1-8 hours to obtain a PVA / CNF-QAS solution.
[0037] S4, after the PVA / CNF-QAS solution is cooled, TA-Fe is added and magnetically stirred evenly, and after drying, a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material is obtained.
[0038] The mass ratio of N,N-dimethyloctylamine to methanol in S1 is 1:(12-18);
[0039] The mass ratio of N,N-dimethyloctylamine to 4-vinylbenzyl chloride in S1 is (3-5):1;
[0040] The concentration of the DMSO solution containing N, N'-carbonyldiimidazole in S2 is 0.2-0.5 mol / L;
[0041] The mass ratio of CNF to bis(carboxymethyl) trithiocarbonate in S2 is 1:(1-2);
[0042] The mass ratio of the intermediate product to QAS in S2 is 1:(1-1.5);
[0043] The mass ratio of CNF-QAS to PVA in S3 is (1% to 7%):1;
[0044] The mass ratio of TA-Fe to PVA in S4 is (0.4% to 1%):1.
[0045] The invention also discloses the macroscopic form of the polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material, which can be a film, electrostatic spinning fiber, aerogel, paper and paperboard, or used as a powder additive in pulp molding materials.
[0046] The invention also discloses the application of the polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material: the material can be widely used in foods not directly ingested, such as fruits and vegetables.
[0047] The specific embodiments are as follows.
[0048] Example 1
[0049] The preparation method of a polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material PVA / CNF-QAS3 / TA-Fe1 in this embodiment comprises the following steps:
[0050] 1) 5.84 g of N, N-dimethyloctylamine was mixed with 100 mL of methanol and stirred to dissolve at -20°C for 2 hours; 1.55 g of 4-vinylbenzyl chloride was slowly added, the temperature was raised to 30°C, and the reaction was continued for 24 hours. After the solvent was removed by rotary evaporation, the mixture was dried in vacuo to obtain QAS.
[0051] 2) 0.5 g of CNF was placed in a DMSO solution containing N, N'-carbonyldiimidazole, the solution concentration was 0.3 mol / L, and the reaction was shielded from light at 40°C for 24 hours, and 0.65 g of bis(carboxymethyl) trithiocarbonate was added as a chain transfer agent and the reaction was continued at 40°C for 48 hours in a light-shielded state. Then, 0.5 g of the intermediate product, 0.5 g of QAS and 10 mg of azobisisobutyronitrile were mixed and dissolved in DMSO, reacted at 60°C for 18 hours, and washed and dried to obtain CNF-QAS.
[0052] 3) PVA was added to the CNF-QAS solution, with the mass ratio of CNF-QAS to PVA being 5:100, and the mixture was heated and stirred at 90° C. for 8 hours to obtain a PVA / CNF-QAS solution.
[0053] 4) After the PVA / CNF-QAS solution is cooled, TA-Fe is added, the mass ratio of TA-Fe to PVA is 0.4%, and the solution is uniformly obtained by magnetic stirring. Then, the obtained solution is poured onto a glass plate and dried at room temperature for 24 hours to obtain a polyvinyl alcohol / amino nanocellulose / tannic acid iron-based high-strength antibacterial food packaging film PVA / CNF-QAS3 / TA-Fe1.
[0054] Example 2
[0055] The preparation method of a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material PVA / CNF-QAS1 / TA-Fe2 in this embodiment includes the following steps:
[0056] 1) 5.84 g of N, N-dimethyloctylamine was mixed with 100 mL of methanol and stirred to dissolve at -20°C for 2 hours; 1.55 g of 4-vinylbenzyl chloride was slowly added, the temperature was raised to 30°C, and the reaction was continued for 24 hours. After the solvent was removed by rotary evaporation, the mixture was dried in vacuo to obtain QAS.
[0057] 2) 0.5 g of CNF was placed in a DMSO solution containing N, N'-carbonyldiimidazole, the solution concentration was 0.3 mol / L, and the reaction was shielded from light at 40°C for 24 hours, and 0.65 g of bis(carboxymethyl) trithiocarbonate was added as a chain transfer agent and the reaction was continued at 40°C for 48 hours in a light-shielded state. Then, 0.5 g of the intermediate product, 0.5 g of QAS and 10 mg of azobisisobutyronitrile were mixed and dissolved in DMSO, reacted at 60°C for 18 hours, and washed and dried to obtain CNF-QAS.
[0058] 3) PVA was added to the CNF-QAS solution, with the mass ratio of CNF-QAS to PVA being 1:100, and the mixture was heated and stirred at 90° C. for 8 hours to obtain a PVA / CNF-QAS solution.
[0059] 4) After the PVA / CNF-QAS solution is cooled, TA-Fe is added, the mass ratio of TA-Fe to PVA is 0.5%, and the solution is uniformly obtained by magnetic stirring. Then, the obtained solution is poured onto a glass plate and dried at room temperature for 24 hours to obtain a polyvinyl alcohol / amino nanocellulose / tannic acid iron-based high-strength antibacterial food packaging film PVA / CNF-QAS 1 / TA-Fe2.
[0060] Example 3
[0061] The preparation method of a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material PVA / CNF-QAS2 / TA-Fe2 in this embodiment includes the following steps:
[0062] 1) 5.84 g of N, N-dimethyloctylamine was mixed with 100 mL of methanol and stirred to dissolve at -20°C for 2 hours; 1.55 g of 4-vinylbenzyl chloride was slowly added, the temperature was raised to 30°C, and the reaction was continued for 24 hours. After the solvent was removed by rotary evaporation, the mixture was dried in vacuo to obtain QAS.
[0063] 2) 0.5 g of CNF was placed in a DMSO solution containing N, N'-carbonyldiimidazole, the solution concentration was 0.3 mol / L, and the reaction was shielded from light at 40°C for 24 hours, and 0.65 g of bis(carboxymethyl) trithiocarbonate was added as a chain transfer agent and the reaction was continued at 40°C for 48 hours in a light-shielded state. Then, 0.5 g of the intermediate product, 0.5 g of QAS and 10 mg of azobisisobutyronitrile were mixed and dissolved in DMSO, reacted at 60°C for 18 hours, and washed and dried to obtain CNF-QAS.
[0064] 3) PVA was added to the CNF-QAS solution, with the mass ratio of CNF-QAS to PVA being 3:100, and the mixture was heated and stirred at 90° C. for 8 hours to obtain a PVA / CNF-QAS solution.
[0065] 4) After the PVA / CNF-QAS solution is cooled, TA-Fe is added, the mass ratio of TA-Fe to PVA is 0.5%, and the solution is uniformly obtained by magnetic stirring. Then, the obtained solution is poured onto a glass plate and dried at room temperature for 24 hours to obtain a polyvinyl alcohol / amino nanocellulose / tannic acid iron-based high-strength antibacterial food packaging film PVA / CNF-QAS2 / TA-Fe2.
[0066] Example 4
[0067] The preparation method of a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material PVA / CNF-QAS3 / TA-Fe2 in this embodiment includes the following steps:
[0068] 1) 5.84 g of N, N-dimethyloctylamine was mixed with 100 mL of methanol and stirred to dissolve at -20°C for 2 hours; 1.55 g of 4-vinylbenzyl chloride was slowly added, the temperature was raised to 30°C, and the reaction was continued for 24 hours. After the solvent was removed by rotary evaporation, the mixture was dried in vacuo to obtain QAS.
[0069] 2) 0.5 g of CNF was placed in a DMSO solution containing N, N'-carbonyldiimidazole, the solution concentration was 0.3 mol / L, and the reaction was shielded from light at 40°C for 24 hours, and 0.65 g of bis(carboxymethyl) trithiocarbonate was added as a chain transfer agent and the reaction was continued at 40°C for 48 hours in a light-shielded state. Then, 0.5 g of the intermediate product, 0.5 g of QAS and 10 mg of azobisisobutyronitrile were mixed and dissolved in DMSO, reacted at 60°C for 18 hours, and washed and dried to obtain CNF-QAS.
[0070] 3) PVA was added to the CNF-QAS solution, with the mass ratio of CNF-QAS to PVA being 5:100, and the mixture was heated and stirred at 90° C. for 8 hours to obtain a PVA / CNF-QAS solution.
[0071] 4) After the PVA / CNF-QAS solution is cooled, TA-Fe is added, the mass ratio of TA-Fe to PVA is 0.5%, and the solution is uniformly obtained by magnetic stirring. Then, the obtained solution is poured onto a glass plate and dried at room temperature for 24 hours to obtain a polyvinyl alcohol / amino nanocellulose / tannic acid iron-based high-strength antibacterial food packaging film PVA / CNF-QAS3 / TA-Fe2.
[0072] Example 5
[0073] The preparation method of a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material PVA / CNF-QAS4 / TA-Fe2 in this embodiment includes the following steps:
[0074] 1) 5.84 g of N, N-dimethyloctylamine was mixed with 100 mL of methanol and stirred to dissolve at -20°C for 2 hours; 1.55 g of 4-vinylbenzyl chloride was slowly added, the temperature was raised to 30°C, and the reaction was continued for 24 hours. After the solvent was removed by rotary evaporation, the mixture was dried in vacuo to obtain QAS.
[0075] 2) 0.5 g of CNF was placed in a DMSO solution containing N, N'-carbonyldiimidazole, the solution concentration was 0.3 mol / L, and the reaction was shielded from light at 40°C for 24 hours, and 0.65 g of bis(carboxymethyl) trithiocarbonate was added as a chain transfer agent and the reaction was continued at 40°C for 48 hours in a light-shielded state. Then, 0.5 g of the intermediate product, 0.5 g of QAS and 10 mg of azobisisobutyronitrile were mixed and dissolved in DMSO, reacted at 60°C for 18 hours, and washed and dried to obtain CNF-QAS.
[0076] 3) PVA was added to the CNF-QAS solution, with the mass ratio of CNF-QAS to PVA being 7:100, and the mixture was heated and stirred at 90° C. for 8 hours to obtain a PVA / CNF-QAS solution.
[0077] 4) After the PVA / CNF-QAS solution is cooled, TA-Fe is added, the mass ratio of TA-Fe to PVA is 0.5%, and the solution is uniformly obtained by magnetic stirring. Then, the obtained solution is poured onto a glass plate and dried at room temperature for 24 hours to obtain a polyvinyl alcohol / amino nanocellulose / tannic acid iron-based high-strength antibacterial food packaging film PVA / CNF-QAS4 / TA-Fe2.
[0078] Example 6
[0079] The preparation method of a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material PVA / CNF-QAS3 / TA-Fe3 in this embodiment includes the following steps:
[0080] 1) 5.84 g of N, N-dimethyloctylamine was mixed with 100 mL of methanol and stirred to dissolve at -20°C for 2 hours; 1.55 g of 4-vinylbenzyl chloride was slowly added, the temperature was raised to 30°C, and the reaction was continued for 24 hours. After the solvent was removed by rotary evaporation, the mixture was dried in vacuo to obtain QAS.
[0081] 2) 0.5 g of CNF was placed in a DMSO solution containing N, N'-carbonyldiimidazole, the solution concentration was 0.3 mol / L, and the reaction was shielded from light at 40°C for 24 hours, and 0.65 g of bis(carboxymethyl) trithiocarbonate was added as a chain transfer agent and the reaction was continued at 40°C for 48 hours in a light-shielded state. Then, 0.5 g of the intermediate product, 0.5 g of QAS and 10 mg of azobisisobutyronitrile were mixed and dissolved in DMSO, reacted at 60°C for 18 hours, and washed and dried to obtain CNF-QAS.
[0082] 3) PVA was added to the CNF-QAS solution, with the mass ratio of CNF-QAS to PVA being 5:100, and the mixture was heated and stirred at 90° C. for 8 hours to obtain a PVA / CNF-QAS solution.
[0083] 4) After the PVA / CNF-QAS solution is cooled, TA-Fe is added, the mass ratio of TA-Fe to PVA is 0.67%, and the solution is uniformly obtained by magnetic stirring. Then, the obtained solution is poured onto a glass plate and dried at room temperature for 24 hours to obtain a polyvinyl alcohol / amino nanocellulose / tannic acid iron-based high-strength antibacterial food packaging film PVA / CNF-QAS3 / TA-Fe3.
[0084] Example 7
[0085] The preparation method of a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material PVA / CNF-QAS3 / TA-Fe2 in this embodiment includes the following steps:
[0086] 1) 5.84 g of N, N-dimethyloctylamine was mixed with 100 mL of methanol and stirred to dissolve at -20°C for 2 hours; 1.55 g of 4-vinylbenzyl chloride was slowly added, the temperature was raised to 30°C, and the reaction was continued for 24 hours. After the solvent was removed by rotary evaporation, the mixture was dried in vacuo to obtain QAS.
[0087] 2) 0.5 g of CNF was placed in a DMSO solution containing N, N'-carbonyldiimidazole, the solution concentration was 0.3 mol / L, and the reaction was shielded from light at 40°C for 24 hours, and 0.65 g of bis(carboxymethyl) trithiocarbonate was added as a chain transfer agent and the reaction was continued at 40°C for 48 hours in a light-shielded state. Then, 0.5 g of the intermediate product, 0.5 g of QAS and 10 mg of azobisisobutyronitrile were mixed and dissolved in DMSO, reacted at 60°C for 18 hours, and washed and dried to obtain CNF-QAS.
[0088] 3) PVA was added to the CNF-QAS solution, with the mass ratio of CNF-QAS to PVA being 5:100, and the mixture was heated and stirred at 90° C. for 8 hours to obtain a PVA / CNF-QAS solution.
[0089] 4) After the PVA / CNF-QAS solution is cooled, TA-Fe is added, the mass ratio of TA-Fe to PVA is 1%, and the solution is uniformly obtained by magnetic stirring. Then, the obtained solution is poured onto a glass plate and dried at room temperature for 24 hours to obtain a polyvinyl alcohol / amino nanocellulose / tannic acid iron-based high-strength antibacterial food packaging film PVA / CNF-QAS3 / TA-Fe4.
[0090] The examples and samples are summarized in the following table.
[0091]
[0092] The polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material prepared by the present invention was characterized as follows:
[0093] 1) Biocompatibility
[0094] The cytotoxicity test is used to evaluate the biocompatibility of the polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material prepared by the present invention, using L929 cells as a model. The PVA / CNF-QAS3 / TA-Fe2 membrane prepared in Example 4 of the present invention was characterized, and the control group selected a PVA membrane and a sample membrane (PVA / CNF-QAS3) without adding TA-Fe. The characterization results of the blank group, the control group and the sample of Example 4 are shown in FIG. Figure 2 As shown. Figure 2It can be seen that the cell viability of L929 cells in culture with PVA membranes is maintained at about 95.2%. After adding CNF-QAS, the cell viability of PVA / CNF-QAS3 is about 93.8%. The PVA / CNF-QAS3 / TA-Fe2 membrane shows excellent biocompatibility, with a cell viability value of 90.5%, which fully complies with the international standard for biomaterials (ISO10993:2009) (≥70%), providing safety protection for food packaging applications.
[0095] 2) Mechanical properties
[0096] The mechanical properties of the PVA / CNF-QAS 1 / TA-Fe2, PVA / CNF-QAS2 / TA-Fe2, PVA / CNF-QAS3 / TA-Fe2, and PVA / CNF-QAS4 / TA-Fe2 films prepared in Examples 2 to 5 of the present invention were characterized, and the stress-strain curves of the materials were investigated. Figure 3 (a); the tensile strength, elongation at break and modulus were extracted and plotted, respectively. Figure 3 (b) Figure 3 (c) and Figure 3 (d). Figure 3 It can be seen that with the increase of CNF-QAS content, the tensile strength and elongation at break of PVA / CNF-QAS / TA-Fe film are improved to a certain extent. The tensile strength of the film increased from 7.6MPa to 11.7MPa, the corresponding modulus increased from 42MPa to 88MPa, and the elongation at break of the film increased from 158% to 200%. This may be due to the good electrostatic interaction, multiple hydrogen bonds and physical entanglement between CNF-QAS and PVA, which ensures the good dispersion of CNF-QAS in PVA and effectively enhances the mechanical properties of the material.
[0097] 3) Barrier properties
[0098] Oxygen and water vapor barrier properties are crucial to food preservation. The oxygen transmission rate (OTR) and water vapor transmission rate (WVTR) of the PVA / CNF-QAS1 / TA-Fe2, PVA / CNF-QAS2 / TA-Fe2, PVA / CNF-QAS3 / TA-Fe2, and PVA / CNF-QAS4 / TA-Fe2 films prepared in Examples 2 to 5 of the present invention were investigated. Figure 3 (e) and Figure 3 (f). Figure 3 (e) and Figure 3 (f) It can be seen that the OTR value of PVA / CNF-QAS / TA-Fe membrane decreases from 6.7 to 4.3 cc / m 2·day, oxygen permeation becomes more difficult with the increase of CNF-QAS addition. In addition, the WVTR value also decreases from 479.9 to 226.3 g / m 2 · days, indicating that the addition of CNF-QAS reduces the hydrophilicity of the film. Therefore, the polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material prepared by the present invention has good oxygen and water vapor barrier properties.
[0099] 4) Antibacterial properties
[0100] The antibacterial properties of the PVA / CNF-QAS3 / TA-Fe2 membrane prepared in Example 4 of the present invention were characterized by using the diffusion plate method to test its anti-E. coli. The control group selected PVA membrane and a sample membrane (PVA / CNF-QAS3) without adding TA-Fe. The characterization results of the blank group, the control group and the sample of Example 4 are shown in Figure 2. Figure 4 As shown. Figure 4 It can be seen that a large number of live colonies proliferated on the LB plate of the blank group. Compared with the blank group, the original PVA film had a slight effect on the survival of Escherichia coli, and near-infrared light irradiation had no significant effect on the antibacterial activity of the PVA film. In addition, for the PVA / CNF-QAS3 film, the presence of CNF-QAS reduced the survival rate of Escherichia coli from 93.7% to 25.5%, respectively, and NIR light irradiation had little effect on the antibacterial activity of PVA / CNF-QAS3. The antibacterial ability of PVA / CNF-QAS3 / TA-Fe2 against Escherichia coli is similar to that of PVA / CNF-QAS3 without near-infrared light irradiation, and the antibacterial rate under near-infrared light radiation can reach 99.9%. Therefore, the above studies have proved that the polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material prepared by the present invention has significant antibacterial ability and has broad application prospects in the field of food packaging.
[0101] 4) Food preservation performance
[0102] By real-time monitoring and recording the appearance images of oranges in different treatment groups, the effect of the PVA / CNF-QAS3 / TA-Fe2 film prepared in Example 4 of the present invention on the storage time of oranges was investigated. Figure 5It can be seen that the unpackaged oranges began to show local mildew on the 6th day of storage, and the mildew became more serious as the storage time increased. A similar phenomenon occurred in the PVA group on the 12th day of storage. A small amount of mold spots appeared in the PVA / CNF-QAS3 group on the 18th day, which may be due to the physical barrier of the membrane and the inhibitory effect of QAS on microorganisms. The PVA / CNF-QAS3 / TA-Fe2 group prepared in Example 4 of the present invention still maintained a good appearance on the 21st day, indicating that the synergistic antibacterial effect of CNF-QAS and TA-Fe can effectively improve the antibacterial activity. It can be seen from the food preservation experiment that the polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material prepared by the present invention has excellent food preservation effect.
[0103] Experimental results show that the polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material prepared by the present invention has good biocompatibility, mechanical properties, water vapor and oxygen barrier properties, antibacterial properties and food preservation properties, and can be widely used in the field of food packaging.
[0104] The invention discloses a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material, comprising polyvinyl alcohol (PVA), hydrophobic quaternary ammonium salt functionalized nanocellulose (CNF-QAS) and tannic acid iron (TA-Fe). The method involves mixing N, N-dimethyloctylamine with methanol in a mass ratio of 1: (12-18), stirring and dissolving at -20°C; slowly adding 4-vinylbenzyl chloride in a mass ratio of (3-5) to 4-vinylbenzyl chloride, raising the temperature to 30°C, and reacting for 24 hours. After removing the solvent by rotary evaporation, vacuum drying is performed to obtain QAS. CNF is placed in a DMSO solution containing N, N'-carbonyldiimidazole, the solution concentration is 0.2-0.5 mol / L, and the reaction is performed at 40°C in a light-shielded state for 24 hours, and bis(carboxymethyl) trithiocarbonate is added as a chain transfer agent and the reaction is continued at 40°C in a light-shielded state for 48 hours, and the mass ratio of CNF to bis(carboxymethyl) trithiocarbonate is 1:(1-2). Then, the obtained intermediate product is mixed with QAS at a mass ratio of 1:(1-1.5) and 10 mg of azobisisobutyronitrile and dissolved in DMSO, and the reaction is performed at 60°C for 18 hours, and the CNF-QAS is obtained by washing and drying. PVA is added to a CNF-QAS solution with a mass ratio of CNF-QAS to PVA of (1% to 7%):1, and the solution is heated at 85 to 110°C and stirred for 1 to 8 hours to obtain a PVA / CNF-QAS solution. After cooling, TA-Fe is added with a mass ratio of TA-Fe to PVA of (0.4% to 1%):1, and the solution is magnetically stirred to be uniform. After drying, a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material is obtained.
[0105] This efficient, economical, biodegradable, high-strength antibacterial food packaging material increases the number of amino functional groups with the help of the quaternary ammonium salt functional groups provided by QAS, and has certain hydrophobicity, mechanical strength and antibacterial properties, which can improve the shortcomings of weak antibacterial effect of single grafted modified materials. At the same time, by virtue of the positively charged amino functional groups of QAS, the binding force between CNF and PVA can be further enhanced through electrostatic action, and the mechanical strength of subsequent food packaging materials can be improved through multiple forces such as van der Waals force, electrostatic action, hydrogen bonding, etc., which can effectively solve the problems of single action and poor mechanical strength in the preparation of materials by existing modification technology. In addition, the introduction of QAS into the material can improve the hydrophobicity of PVA / CNF composite materials and effectively realize the barrier properties and water resistance of the material. By simply mixing tannic acid solution and FeCl3·6H2O solution to prepare the coordination complex tannic acid iron, adding it to the material can synergistically enhance the antibacterial properties of traditional materials. Under near-infrared laser triggering, the material has high precision and broad-spectrum antibacterial activity, which can effectively achieve antibacterial and antibacterial. The preparation method of the food packaging material is simple, the reaction conditions are mild, the reactants have low toxicity, and the reaction process is relatively safe. The process is both economical and simple, and can be widely used in food packaging; the prepared material has good degradability and biocompatibility, which is beneficial to the sustainable development of the environment; and the reaction raw materials are widely available, which is beneficial to the promotion and application of the material.
Claims
1. A polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material, characterized in that: The material mainly comprises polyvinyl alcohol, hydrophobic quaternary ammonium salt functionalized nanocellulose and tannic acid iron, and based on the mass of polyvinyl alcohol, the mass of hydrophobic quaternary ammonium salt functionalized nanocellulose accounts for 1% to 7%, and the mass of tannic acid iron accounts for 0.4% to 1%. The preparation method of the material comprises the following steps: Step 1, mixing N, N-dimethyloctylamine and methanol in a mass ratio of 1: (12-18), and stirring and dissolving at -20°C; slowly adding 4-vinylbenzyl chloride, the mass ratio of N, N-dimethyloctylamine to 4-vinylbenzyl chloride is (3-5): 1, raising the temperature to 30°C, and reacting for 24 hours; after removing the solvent by rotary evaporation, vacuum drying, and obtaining a hydrophobic quaternary ammonium salt functionalization reagent; Step 2, placing the nanocellulose in a dimethyl sulfoxide solution containing N, N'-carbonyldiimidazole, the concentration of N, N'-carbonyldiimidazole is 0.2-0.5 mol / L, and reacting at 40°C in a dark environment for 24 hours, and adding bis(carboxymethyl) trithiocarbonate as a chain transfer reagent, the mass ratio of nanocellulose to bis(carboxymethyl) trithiocarbonate is 1:(1-2), and continuing to react at 40°C in a dark environment for 48 hours; then, the reaction product of the nanocellulose and bis(carboxymethyl) trithiocarbonate is mixed with a hydrophobic quaternary ammonium salt functionalizing agent at a mass ratio of 1:(1-1.5) and dissolved in dimethyl sulfoxide, and 10 mg of azobisisobutyronitrile is added at 60°C for 18 hours, and washed and dried to obtain hydrophobic quaternary ammonium salt functionalized nanocellulose; Step 3, adding polyvinyl alcohol to the hydrophobic quaternary ammonium salt functionalized nanocellulose solution, the mass ratio of hydrophobic quaternary ammonium salt functionalized nanocellulose to polyvinyl alcohol is (1% to 7%): 1, heating and stirring at 85 to 110° C. for 1 to 8 hours to obtain a polyvinyl alcohol / hydrophobic quaternary ammonium salt functionalized nanocellulose solution; Step 4, after the polyvinyl alcohol / hydrophobic quaternary ammonium salt functionalized nanocellulose solution is cooled, tannic acid iron is added, the mass ratio of tannic acid iron to polyvinyl alcohol is (0.4% to 1%):1, and magnetic stirring is performed to obtain a polyvinyl alcohol / nanocellulose / tannic acid iron-based high-strength food packaging material after drying.
2. A polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material according to claim 1, characterized in that: The macroscopic forms are powder additives for membranes, electrospun fibers, aerogels, paper, and pulp molding.
3. A polyvinyl alcohol / nanocellulose / ferric tannate-based high-strength food packaging material according to claim 1, characterized in that: For food not intended for direct consumption.
Citation Information
Cited By
Mechanical reinforcement type Janus active PVA composite film and preparation method and application thereof
CN122520961A